CINTA DAN EKOTEOLOGI BAGI MASA DEPAN MALUKU: PERSPEKTIF PEKERJAAN SOSIAL DALAM MEMBANGUN KEADILAN EKOLOGIS - Korneles Balak; Hobarth Williams Soselisa (JURNAL BADATI, 2026)
This article examines how the concepts of love and ecotheology can contribute to the future of Maluku from a social work perspective by employing the person-in-environment approach and a socio-ecological framework (Germain & Gitterman, 1996; Karls & Wandrei, 1994). Ecological degradation in Maluku is understood as a socio-ecological crisis that affects the social functioning and well-being of coastal communities and small-island societies (Manusama, 2021). Love is conceptualized as a relational and ethical principle that connects God, human beings, and all creation, while ecotheology is understood as a critical theological response to ecological injustice (eco-justice) (Boff, 1997; Santmire, 2000). Using a descriptive qualitative research method based on library research, this study examines various literatures on ecotheology, the local wisdom of sasi, and environmental social work (Coates et al., 2012; Gray et al., 2013). The findings indicate that the integration of love, ecotheology, and social work can serve as a conceptual framework for strengthening ecological advocacy, community empowerment, revitalizing sasi practices, and developing ecological communities in Maluku (Närhi & Matthies, 2018). This article recommends strengthening ecotheology-based social work curricula, recognizing sasi practices within public policy frameworks, and fostering cross-sector collaboration among churches, customary institutions, government agencies, and social work professionals to promote a just and sustainable future for Maluku (IFSW, 2018; La Masaka, 2024).